2020
DOI: 10.1007/s40123-020-00306-1
|View full text |Cite
|
Sign up to set email alerts
|

Post-FDA Approval Results of Epithelium-Off, Full-Fluence, Dresden Protocol Corneal Collagen Crosslinking in the USA

Abstract: Introduction: The purpose of this non-comparative, prospective, observational study was to evaluate the post-US Food and Drug Administration approval outcomes of epithelium-off, full-fluence, Dresden protocol corneal collagen crosslinking (CXL) for the treatment of progressive keratoconus (KCN) and post-refractive corneal ectasia at a US academic tertiary medical center. Methods: This study involved 125 eyes of 97 patients with KCN and 13 eyes of 12 patients with post-refractive ectasia which underwent CXL bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A prior study reported that pediatric central and paracentral corneal thicknesses increase slowly but did not elaborate on the reason for this phenomenon [ 37 ]. However, MCT changes did not significantly differ between adult and pediatric patients at 2 and 4 years after CXL [ 38 , 39 ]. A longer term follow-up is therefore needed to validate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study reported that pediatric central and paracentral corneal thicknesses increase slowly but did not elaborate on the reason for this phenomenon [ 37 ]. However, MCT changes did not significantly differ between adult and pediatric patients at 2 and 4 years after CXL [ 38 , 39 ]. A longer term follow-up is therefore needed to validate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, epithelium-off CXL is the only FDA-approved treatment that has been reported to slow or halt the progression of KC in its early to moderate stages, with numerous studies supporting its efficacy [ 7 , 8 , 11 ]. A previous study of bilateral sequential CXL versus delayed CXL demonstrated progression in 27% of the patients in the delayed group, and an economical analysis for the office visits saved showed that immediate CXL may be a less costly approach than delayed CXL [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All subjects gave informed consent to participate in this study. A patient registry was compiled consisting of a cohort of 104 subjects with KC that initially underwent unilateral epithelium-off, using the Dresden protocol CXL, in the worse eye, between November 2016 and July 2019 as described in our previous study [ 11 ]. Of the 104 subjects, 12 eyes with laser-assisted in situ keratomileusis (LASIK)-induced ectasia and 12 subjects with a follow-up of less than six months were excluded from this analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] A recent US study assessing the effects of epitheliumoff crosslinking in both keratoconus and postrefractive ectasia in 39 pediatric eyes demonstrated improvement in maximum keratometry (Kmax) and stability in visual acuity over 24 months. 6 Long-term outcomes outside the United States after crosslinking for pediatric keratoconus have also been promising. Mazzotta et al 7 assessed 62 eyes of 47 patients younger than 18 years with progressive keratoconus and showed that both uncorrected and corrected distance visual acuity (CDVA) were significantly improved in most eyes after 10 years.…”
mentioning
confidence: 99%